Kolaborasi Dinas Perhubungan Dan Kepolisian Dalam Penertiban Kendaraan Tidak Layak Jalan Di Kabupaten Gianyar - I Putu Amerta Yoga Mahardika Sangging; I Gusti Bagus Hengki (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
This study focuses on the collaboration between the Transportation Agency and the Police in controlling unroadworthy vehicles in Gianyar Regency as an effort to improve traffic safety and order. The enforcement is carried out through coordinated mechanisms and in accordance with Law Number 22 of 2009 on Road Traffic and Transportation. The collaboration is implemented through public socialization, technical vehicle inspections, and joint operations, in which the Transportation Agency is responsible for technical vehicle aspects, while the Police conduct law enforcement against violations. The type of research used in this thesis is empirical legal research with a qualitative approach, conducted through field research by collecting primary and secondary data. The results show that the collaboration between the two institutions has been relatively effective; however, it still faces obstacles such as low public awareness, limited personnel and facilities, widespread Over Dimension Over Load (ODOL) violations, and the low deterrent effect of imposed sanctions